PXL01 in sodium hyaluronate results in increased PRG4 expression: a potential mechanism for anti-adhesion. (2nd January 2017) - Edsfeldt, Sara; Holm, Björn; Mahlapuu, Margit; Reno, Carol; Hart, David A.; Wiig, Monica
Abstract: Purpose: To investigate the anti-adhesive mechanisms of PXL01 in sodium hyaluronate (HA) by using the rabbit lactoferrin peptide, rabPXL01 in HA, in a rabbit model of healing tendons and tendon sheaths. The mechanism of action for PXL01 in HA is interesting since a recent clinical study of the human lactoferrin peptide PXL01 in HA administered around repaired tendons in the hand showed improved digit mobility. Materials and methods: On days 1, 3, and 6 after tendon injury and surgical repair, reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) was used to assess mRNA expression levels for genes encoding the mucinous glycoprotein PRG4 (also called lubricin) and a subset of matrix proteins, cytokines, and growth factors involved in flexor tendon repair. RabPXL01 in HA was administered locally around the repaired tendons, and mRNA expression was compared with untreated repaired tendons and tendon sheaths. Results: We observed, at all time points, increased expression of PRG4 mRNA in tendons treated with rabPXL01 in HA, but not in tendon sheaths. In addition, treatment with rabPXL01 in HA led to repression of the mRNA levels for the pro-inflammatory mediators interleukin (IL)-1β, IL-6, and IL-8 in tendon sheaths. Conclusions: RabPXL01 in HA increased lubricin mRNA production while diminishing mRNA levels of inflammatory mediators, which in turn reduced the gliding resistance and inhibited the adhesion formation after flexor tendon repair.